Falling film on a vertical flat plate – Influence of liquid distribution and fluid properties on wetting behavior. (August 2017) - Lu, Yan; Stehmann, Friederike; Yuan, Sijia; Scholl, Stephan
Highlights: Number of distributor holes influences wetting only before a plate is totally wetted. The minimum wetting rate decreases with an increasing Kapitsa number. Normalization with characteristic length captures influence of physical properties. Abstract: Complete and even wetting of the surface with a thin liquid film is essential in falling film units for heat or mass transfer. This work presents the influence of different liquid distribution systems and physical properties of the working fluid on the wetting behavior on a vertical flat plate. The wetting behavior is characterized by the film thickness, wetted coverage and minimum wetting rate. These parameters were experimentally determined for film Reynolds numbers of 0.5 ≤  ReF  ≤ 460 with the fluorescence intensity technique. Two distributor hole arrangements with similar cross-sectional areas were compared. Furthermore, the wetting behavior of water and water/glycerol mixtures with Kapitsa numbers of 1.6 · 10 −11  ≤  Ka  ≤ 3.9 · 10 −6 was investigated. The minimum wetting rate differs in wetting and dewetting experiments and with physical properties of the working fluid. It is compared with the prediction of different literature theories. A general equation with an uncertainty of ±10% capable to describe the normalized mean film thickness of all measured liquids in dependency of film Reynolds number is presented.